A Potential Peptide Therapeutic Derived from the Juxtamembrane Domain of the Epidermal Growth Factor Receptor - Boran, Aislyn D. W. (Public Library of Science, 2012)
The epidermal growth factor receptor (EGFR) is involved in many cancers and EGFR has been heavily pursued as a drug target. Drugs targeting EGFR have shown promising clinical results for several cancer types. However, resistance to EGFR inhibitors often occurs, such as with KRAS mutant cancers, therefore new methods of targeting EGFR are needed. The juxtamembrane (JXM) domain of EGFR is critical for receptor activation and targeting this region could potentially be a new method of inhibiting EGFR. We hypothesized that the structural role of the JXM region could be mimicked by peptides encoding a JXM amino acid sequence, which could interfere with EGFR signaling and consequently could have anti-cancer activity. A peptide encoding EGFR 645–662 conjugated to the Tat sequence (TE-64562) displayed anti-cancer activity in multiple human cancer cell types with diminished activity in non-EGFR expressing cells and non-cancerous cells. In nude mice, TE-64562 delayed MDA-MB-231 tumor growth and prolonged survival, without inducing toxicity. TE-64562 induced non-apoptotic cell death after several hours and caspase-3-mediated apoptotic cell death with longer treatment. Mechanistically, TE-64562 bound to EGFR, inhibited its dimerization and caused its down-regulation. TE-64562 reduced phosphorylated and total EGFR levels but did not inhibit kinase activity and instead prolonged it. Our analysis of patient data from The Cancer Genome Atlas supported the hypothesis that down-regulation of EGFR is a potential therapeutic strategy, since phospho- and total-EGFR levels were strongly correlated in a large majority of patient tumor samples, indicating that lower EGFR levels are associated with lower phospho-EGFR levels and presumably less proliferative signals in breast cancer. Akt and Erk were inhibited by TE-64562 and this inhibition was observed in vivo in tumor tissue upon treatment with TE-64562. These results are the first to indicate that the JXM domain of EGFR is a viable drug target for several cancer types.